Role of UNSIKA in Building City Branding in Karawang Regency - Fajar Ramadhan; Ajat Sudrajat (Fakultas Ekonomi, Universitas Bangka Belitung, 2017)
Seeing the steps of city branding that has been done, in general, seems more severe to the development of tourism destinations, especially attract tourists. In fact, city branding should also be able to bring investment and increase trade in the city. Most of the regions and cities/districts in Indonesia, including Karawang regency, merely promoted, has not raised a unique and emotional side. City Branding is an urban economic development tool. City Branding is a tool borrowed from marketing practices by city planners and designers and all stakeholders. As products, services and organizations, cities need a strong reputation and the image of a different order to overcome the competition for resources city economy in local, regional, national and global. The role of UNSIKA as a party that facilitate the efforts of city branding development Karawang regency. As the heart of the information providing support of data as well as a catalyst for policies taken by the government concerned, as well as controlling the sustainability of efforts to build a city branding this as a joint activity between the government and the public joined in the development of Agriculture, Industry MSMEs (Micro, Small and Medium) and IKM (Small and Medium Industry). In addition, the human resources that exist in UNSIKA will greatly assist the process of assistance for farmers, industry, and SMEs that exist. It is hoped that the presence of universities will contribute directly in the evaluation of regional development programs and regional development planning that is in synergy with the community, and indirectly can help provide training and thought contribution in the process of management Karawang regency.